Pollinating potential of bee floral visitors of Spondias mombin (Anacardiaceae) cultivated in northeastern Brazil (Research, Society and Development, 2020)
To better understand the relationship between Spondias mombin (Anacardiaceae) with its floral visitors, we investigated stigma receptivity and flowering pattern, as well as the abundance, frequency and behavior of bees visiting its flowers, aiming to discuss their potential as pollinator of this plant species. We studied S. mombin in an orchard in Northeastern Brazil. Stigma receptivity coincided with the time bees were foraging, mainly for pollen. According to the bee behavior on flowers, their visiting hour, abundance, and frequency in the studied area, we concluded that Apis mellifera (Linnaeus), Trigona spinipes (Fabricius), Xylocopa grisescens (Lepeletier) and Augochloropsis sp. are potential pollinators of S. mombin. Also, A. mellifera and T. spinipes were the most abundant species in the area and collected floral resources with greater frequency, contributing more significantly to pollination. Due to the overwhelmingly presence of these two bee species in NE Brazil, we conclude they are the main potential pollinators of S. mombin in the region.